ANALISIS PENYAJIAN FOTO BERITA PADA SURAT KABAR HARIAN UMUM RAKYAT BENGKULU - Fardiana - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
In journalistic work, photo has a very important role, such as beautify the pages and make the reader does not get tired reading. Each incoming photojournalism was selected by the photo editor to be considered whether a photo was appropriate and decent published in accordance with the written word. This research used observation and interview techniques to collect data. Data analysis techniques used by researcher was a descriptive analysis of data processing techniques. The photos presented Harian Rakyat Bengkulu were color photos and black and white photos. Based on the results of the discussion and explanation of this research from February 14 to March 14, it could be concluded that: The photos displayed on Harian Rakyat Bengkulu had various types which include spot News, Human Interest, Photo story, Feature Photo, and Photo Document. But of the many photos attached, most photos appearing in each edition were Spot News and stories.Keywords: photo, news, newspaper